The Effect of Earnings Quality on Cost of Equity Through Information Asymmetry: An Empirical Study of the Manufacturing Companies in the Indonesia Stock Exchange - Dewi Melinda; Zuni Barokah (The Indonesian Journal of Accounting Research, 2019)
This research examines the effect of earnings quality on the cost of equity and whether information asymmetry affects the relationship as a mediator. A hundred and twenty-three manufacturing companies listed in the Indonesia Stock Exchange during 2007-2012 were selected through a purposive sampling method. This study uses absolute discretionary accruals (|DA|) to measure earnings quality, bid-ask spread to proxy information asymmetry, and CAPM to measure the cost of equity. Using the bootstrapping method in the hypotheses testing, this study finds a significant negative effect of earnings quality on the information asymmetry. However, there is no support on the positive association between information asymmetry and the cost of equity, as well as the role of information asymmetry as a mediator on the negative association between earnings quality and cost of equity.